A study of online financial reporting research - Ali Khan, Mohd Noor Azli; Ismail, Noor Azizi (2011)
Internet is a very interesting medium to look into especially with regards to financial reporting and disclosure. The Internet also has become one of users’ most frequently used sources of information. Consistent with the advancement of the Internet as a cheap but powerful communication device, disclosure of financial and non-financial information on the Internet is becoming an increasingly popular subject of research. Internet reporting is a very powerful and useful tool for financial reporting information. Internet Financial Reporting (IFR) has become quite a popular practice of communicating with stakeholders in recent times. World Wide Web (WWW) technologies are extensively used by ever-increasing number of companies around the world. A growing percentage of those companies have created and promoted websites on the Internet. There have been tendencies to disseminate information on their websites, including financial data, financial performance, social and environmental issues, corporate governance, marketing and other information. At this point, a significant amount of academic research has been establish in the area of IFR in developed countries such as the United States, United Kingdom and other European countries. On the contrary, very few studies were carried out in developing countries. Previous IFR studies are divided into three main groups: single-country studies, multi-country studies and international studies. Methodologically, studies on IFR are categorized into three main groups: descriptive research, comparative research and explanatory research. This paper seeks to contribute to the existing body of knowledge concerning financial reporting online by reviewing and documenting the research of IFR.